Predator Cues Increase Silkmoth Mortality - Baranowski, Alex K.; Preisser, Evan L. (Frontiers in Ecology and Evolution, 2018)
While prey responses to predators reduce the threat of consumption, the physiological costs of these responses can be considerable. This is especially true for organisms that lack effective anti-predator defenses and must rely on camouflage or mimicry for protection. The luna moth, Actias luna, is a large saturniid native to Eastern North America that is preyed on by a wide variety of predators and parasitoids. We report the results of two separate experiments assessing the responses of Actias larvae to predatory wasps (Vespula maculifrons) that were rendered non-lethal but remained able to move freely, as well as in a control (wasp-free) treatment. We determined whether these responses were predator-specific by also testing the response of Actias larvae to a similarly-sized but harmless scavenging fly. In both experiments, A) Actias larvae in the wasp treatment died at a higher rate than those in the control treatments; and B) larval survival in the fly and control treatments did not differ. Despite similar Actias survival in the fly and control treatments, fly-treatment larvae that died appeared to respond similarly to flies as other larvae did to wasps. In both years, larvae that died in the fly and wasp treatments gained virtually no weight between the start of the experiment and their death, suggesting that they may have succumbed to starvation. Our results, replicated over two years, illustrate the high cost of anti-predator responses and are the first report of lethal risk effects in caterpillars.